DAMPAK KEBIJAKAN PELARANGAN PENGGUNAAN CANTRANG PADA NELAYAN CANTRANG DI KECAMATAN BRONDONG KABUPATEN LAMONGAN - Alfi Azhari Hanum; Saiman Saiman; Iradhad Taqwa Sihidi (Jurnal Agregasi : Aksi Reformasi Government dalam Demokrasi, 2021)
This study aims to see the impact of the cantrang prohibition policy issued by the Ministry of Fisheries and Marine Affairs in Brondong District, Lamongan Regency. Through the Regulation of the Minister of Marine Affairs and Fisheries Number 2 of 2015 concerning the Prohibition of Using Hela Trawl and Trawling Fishing Tools in the WPPNRI article 4 paragraph (2), the Indonesian government wants to maintain the sustainability of Indonesia's marine resources which at the same time has negative implications for the income of fishermen and other parties. others. This research is categorized into a descriptive qualitative type, the data obtained using the direct interview method, observation, and documentation that supports this research. Research shows that fishermen and related parties have suffered significant losses due to drastically reduced fish catch, which is contagious to the sluggishness of fish auction and boat building services. There is resistance from fishermen to this policy which can be resolved. Keywords: Policy Impact, Cantrang Policy, Cantrang.